Future home of the living god a novel - Erdrich, Louise 1954- (Harper, 2017)
The world as we know it is ending. Evolution has reversed itself, affecting every living creature on earth. Science cannot stop the world from running backwards, as woman after woman gives birth to infants that appear to be primitive species of humans. Twenty-six-year-old Cedar Hawk Songmaker, adopted daughter of a pair of big-hearted, open-minded Minneapolis liberals, is as disturbed and uncertain as the rest of America around her. But for Cedar, this change is profound and deeply personal. She is four months pregnant. Though she wants to tell the adoptive parents who raised her from infancy, Cedar first feels compelled to find her birth mother, Mary Potts, an Ojibwe living on the reservation, to understand both her and her baby's origins. As Cedar goes back to her own biological beginnings, society around her begins to disintegrate, fueled by a swelling panic about the end of humanity. There are rumors of martial law, of Congress confining pregnant women. Of a registry, and rewards for those who turn these wanted women in. Flickering through the chaos are signs of increasing repression: a shaken Cedar witnesses a family wrenched apart when police violently drag a mother from her husband and child in a parking lot. The streets of her neighborhood have been renamed with Bible verses. A stranger answers the phone when she calls her adoptive parents, who have vanished without a trace. It will take all Cedar has to avoid the prying eyes of potential informants and keep her baby safe
Keywords: Dystopian fiction / fast / (OCoLC)fst01921637; Fiction / fast / (OCoLC)fst01423787; Dystopias / gsafd; Dystopian fiction / lcgft; Fiction / lcgft; Dystopian fiction / sears; FICTION / Dystopian / bisacsh; FICTION / Political / bisacsh; FICTION / Visionary & Metaphysical / bisacsh; Adoptees / fast / (OCoLC)fst00797063; Authoritarianism / fast / (OCoLC)fst00821640; Birthmothers / fast / (OCoLC)fst00833291; End of the world / fast / (OCoLC)fst00909634; Ojibwa Indians / fast / (OCoLC)fst01045067; Pregnant women / fast / (OCoLC)fst01075191; Pregnancy / Fiction / sears; Adoptees / Fiction / sears; Ojibwa Indians / Fiction / sears; Pregnant women -- Fiction; Adoptees -- Fiction; Authoritarianism -- Fiction; Birthmothers -- Fiction; Ojibwa Indians -- Fiction; End of the world -- Fiction; Ojibwa Indians; Pregnancy; Adoptees; FICTION / Dystopian; FICTION / Political; FICTION / Visionary & Metaphysical; Authoritarianism; Birthmothers; End of the world; Pregnant women; Minnesota / fast / (OCoLC)fst01204560; Minnesota -- Fiction; Minnesota; Fiktionale Darstellung